Progenitor recruitment and adipogenic lipolysis contribute to the anabolic actions of parathyroid hormone on the skeleton. Issue 2 (24th October 2018) - Maridas, David E.; Rendina-Ruedy, Elizabeth; Helderman, Ron C.; DeMambro, Victoria E.; Brooks, Daniel; Guntur, Anyonya R.; Lanske, Beate; Bouxsein, Mary L.; Rosen, Clifford J.
ABSTRACT: Intermittent administration of parathyroid hormone (PTH) stimulates bone formation in vivo and also suppresses the volume of bone marrow adipose tissue (BMAT). In contrast, a calorie‐restricted (CR) diet causes bone loss and induces BMAT in both mice and humans. We used the CR model to test whether PTH would reduce BMAT in mice by both altering cell fate and inducing lipolysis of marrow adipocytes. Eight‐week‐old mice were placed on a control (Ctrl) diet or CR diet. At 12 wk, CR and Ctrl mice were injected daily with PTH (CR/PTH or Ctrl/PTH) or vehicle for 4 wk. Two other cohorts were CR and simultaneously injected (CR + PTH or CR + Veh) for 4 wk. CR mice had low bone mass and increased BMAT in the proximal tibias. PTH significantly increased bone mass in all cohorts despite calorie restrictions. Adipocyte density and size were markedly increased with restriction of calories. PTH reduced adipocyte numbers in CR + PTH mice, whereas adipocyte size was reduced in CR/PTH‐treated mice. In contrast, osteoblast number was increased 3–8‐fold with PTH treatment. In vitro, bone marrow stromal cells differentiated into adipocytes and, treated with PTH, exhibited increased production of glycerol and fatty acids. Moreover, in cocultures of bone marrow adipocyte and osteoblast progenitors, PTH stimulated the transfer of fatty acids to osteoblasts. In summary, PTH administration to CR mice increased bone mass by shifting lineage allocation toward osteogenesis and inducing lipolysis of mature marrow adipocytes. The effects of PTH on bone marrow adiposity could enhance its anabolic actions by providing both more cells and more fuel for osteoblasts during bone formation.—Maridas, D. E., Rendina‐Ruedy, E., Helderman, R. C., DeMambro, V. E., Brooks, D., Guntur, A. R., Lanske, B., Bouxsein, M. L., Rosen, C. J. Progenitor recruitment and adipogenic lipolysis contribute to the anabolic actions of parathyroid hormone on the skeleton. FASEB J. 33, 2885–2898 (2019). www.fasebj.org